The impact of citizen activism on the political economy of Zimbabwe. A case study of Tajamuka/Sesjikile campaign (2016-2017) in Beitbridge town. - Mleya, Innocent (Midlands State University, 2020)
Through the use of qualitative and quantitative research, at large documentary review, this study focuses on the impact of citizen activism on the political economy of Zimbabwe. The study is based on Tajamuka/ Sesijikile campaign which embarked and still today offer efforts on organized action against the government of Zimbabwe under Zanu pf regime during 2016 to date. It is from the realization that current citizen activism in Zimbabwe has proved to be having a punch towards calling for a multifaceted reforms, hence the researcher chose to unravel such prominent issues pertaining citizen participation I politics and the third wave democracy were people are airing their views through various means, amongst those is the use of social media. The researcher chose Beitbridge Town as the main site since some vibrant action started in Beitbridge town which in deeper criticism can be seen as one of the actions which perpetrated movements to other towns like Harare and Bulawayo. Prominent government response took root after Tajamuka/Sesijikile campaign and the Cross Border Association collectively flooded Beitbridge town blocking main roads, vandalizing the government property and burning the ZIMRA warehouse. Anticorruption measures like the multi transfers of different officers from government parastatals like the VID, ZIMRA and ZRP in Beitbridge. The turning reversal of the Statutory Instrument also marked to effective efforts by the activists towards informal business. Through the lens of social movement and new social movement theories, the paper argues that while the social media platform have an impact on the mobilization of action, it goes without say that the outcomes of the action detects the its impact. The paper ends by outlining for discursive opportunities and possibilities of the future of citizen activism in Zimbabwe.